In Vitro Susceptibility of Nocardia asteroides to Amikacin - Dalovisio, Joseph R. (1978)
By drug dilution tests in agar, it has been shown that each of 27 strains of Nocardia asteroides was inhibited by 1 μg or less of amikacin per ml of medium.